Psychiatric Nursing Care Process with NANDA, NIC, and NOC Classifications: Case Example - Tuğba Şahin Tokatlıoğlu; Fahriye Oflaz (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Nursing care plans present a systematic way and standard language for nurses. Standardized care terminology and evaluations are important in providing a common language globally and showing nursing care outcomes. The North American Nursing Diagnosis Association Taxonomy, Nursing Interventions Classification, and Nursing Outcomes Classification form the structure of the nursing care plans. This standardized nursing process language provides a system that supports individualized care, allowing us to visualize and formulate a nursing process. The aim of this study is to present an example of the use of the North American Nursing Diagnosis Association Taxonomy, Nursing Interventions Classification, and Nursing Outcomes Classification system in the care process of a 42-year-old individual with a diagnosis of bipolar disorder.